Enhancement of the growth and yield of wheat in coastal saline areas through organic and inorganic amendments (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Salinity is a major limiting factor reducing crop yields in coastal areas of Bangladesh. The main objective of this study was to mitigate the adverse effects of soil salinity on wheat by organic and inorganic amendments. The field experiment was conducted at BRRI station, Sonagazi, Feni. Wheat cv. BARI Gom-23 was used as a test crop. There were thirteen treatment combinations consisting of control, farmyard manure (FYM) (5 t ha-1), FYM (10 t ha-1), compost (10 t ha-1), compost (20 t ha-1), gypsum (50% GR), gypsum (100% GR), K2SO4 (100 kg ha-1), K2SO4 (200 kg ha-1), FYM (5 t ha-1) + gypsum (50% GR), FYM (5 t ha-1) + K2SO4 (100 kg ha-1), compost (10 t ha-1) + gypsum (50% GR), compost (10 t ha-1) + K2SO4 (100 kg ha-1). FYM and compost were added to the soils during final land preparation. Gypsum and sulphate of potash were applied in two splits as per treatments. Nitrogen, phosphorous, zinc and boron fertilizers were applied as basal doses. The experiments were laid out in a randomized complete block design with three replications. Soil salinity caused a reduction in growth and yield of wheat. Soil amendments with organic or inorganic fertilizers improved growth and yield of wheat under soil salinity. Combined application of organic and inorganic fertilizers showed higher yields of wheat than that of alone during salinity conditions. Both organic and inorganic fertilizers increased nutrient uptake and K+/Na+ ratio in wheat during salinity condition. Therefore, the present study suggests that wheat production might be feasible in coastal areas of southern Bangladesh through organic and inorganic amendments of saline soils.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 169-175